A Korean Case Study of OTT Platforms Based on Hesmondhalgh and Baker’s Theoretical Framework - Ryoo, Kyuha (Journal of Posthumanism, 2025)
The rapid expansion of streaming platforms and OTT services is fundamentally reshaping traditional film production practices. This study draws on in-depth interviews with film producers and outsourced martial arts directors, who have worked on both Netflix originals and commercial films, as well as on prior research, to examine how Netflix’s production system influences the economic, institutional, and administrative landscape of Korean film production labor—and its effect on creative autonomy and identity. Applying the “good work” versus “bad work” framework proposed by Hesmondhalgh and Baker, the analysis reveals both positive and negative facets. On the positive side, long-term contracts, global exposure, and considerable creative freedom for key creators have been observed. Conversely, issues such as burdensome production reporting, frequent meetings with headquarters, and inadequate insurance systems intended to reduce costs present challenges. Remarkably, the study also finds that for lower-tier production staff, the working conditions in both traditional commercial films and Netflix projects are largely indistinguishable, suggesting that conventional practices persist within certain outsourced sectors. Overall, the results indicate that Korean Netflix original productions generally meet the criteria for “good work” in terms of their final outcomes and social contributions. However, they also underscore the urgent need for policy measures aimed at streamlining administrative processes and enhancing labor protection.